ANALISIS KETERAMPILAN TEKNIK DASAR PEMAIN SEPAKBOLA SEKOLAH SEPAKBOLA (SSB) BENGKULU MUDA - Septian, Vero; Sumantri, Ajis; Dewi, Citra (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
The problem in this study is not maximized in heading, passing, shooting, dribbling, and control, especially U-10 years. Therefore this study aims to determine the analysis of the basic technical skills of soccer players of Bengkulu soccer school (SSB).This type of research is descriptive research. The population in this study were 50 players who came from SSB Bengkulu players. Sample withdrawal is done with data collection techniques using proposive sampling. The sample in this study were 50 SSB Bengkulu players with specifications of 15 people aged 8, 15 people aged 10 and 20 people aged 12. The research instrument was a basic soccer technique test. Analysis of research data using frequency distribution techniques with percentage calculations P = F / N x100%. Based on the results of the study that 1) dribbling skills are in the